Socio-cultural and economic nature of tourism and its methodological basis - Huseynov, Ilgar Hasrat Oglu (Technium Social Sciences Journal, 2023)
In modern times, tourism, which is seen as a sphere of socio-cultural and economic activity in a globalized world, is also of particular importance in terms of conceptualization and scientific research. Today, tourism is valued not only as a type of activity, the sphere of recreation and entertainment, but also as one of the leading areas of the national economy. The increase in the number of tourists, the expansion of business, advertising and marketing ties increases the sense of responsibility and accountability of companies and institutions working in this area. In particular, the development of tourism in less developed countries is considered one of the most effective tools to combat poverty. Research shows that there is a positive and direct relationship between social security and tourism. Tourism, which plays an important role in the economy of the countries of the world, is of global interest. To date, there are close financial relationships between logistics and transport enterprises operating in the tourism sector, accommodation centers, tour operators, catering enterprises and enterprises providing entertainment services. The active role of tourism in the national economy is characterized by changes in the creation of national income, the contribution of tourism to the balance of payments, and tax revenues to the budget. The influence of tourism on the world community is constantly growing, which has taken an exceptional position in spreading the atmosphere of global peace and security and reducing international tension. The growth of tourist exchange, the strengthening of peace between states and good neighborly relations play an important role in the formation of healthy communication. At the same time, the socio-economic and cultural significance of tourism encourages the creation of specialized organizations.